Perkembangan Penelitian di Bidang Teknologi Membran Menggunakan Pendekatan Cellulose Acetate Mixed Matrix Membrane: Studi Analisis Bibliometrik - Panggulu Ahmad Ramdhani Utoro; Imam Rosadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The development of science needs to be done so that research gaps can be traced and known so that sustainable research occurs. In this study, a bibliometric analysis approach was carried out with the keywords "cellulose acetate mixed matrix membrane". The data was obtained from the Scopus portal using Publish or Perish (PoP) software with a search range of 2001 to 2022. The data obtained was then analyzed using the 2019 version of Microsoft Excel and VosViewer. PoP search results show that from 2001 to 2022 there were 137 articles. There is an increase in the number of documents with the year of the search. The highest number of article documents in 2020 was 26 articles. with the number of documents, the trend of the highest number of citations was obtained in the range of 2010 â€“ 2014. Portal Journal of Membrane Science is a journal that reports the most different data related to these keywords as many as 12 articles. The most prolific writer as a correspondent writer is Mubashir, M with a total of 6 articles. The most frequently encountered keywords in article manuscripts were â€œcellulose acetateâ€, â€œmixed matrix membraneâ€, and â€œfabricationâ€. The three keywords form three interrelated clusters.